The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201500218
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Anderson‐Type Polyoxometalates to Single‐Walled Carbon Nanotubes Gives Enhanced Performance Electrodes for Lithium Ion Batteries

Abstract: Single-walled carbon nanotubes (SWNTs) covalently functionalized with redox-active organo-modified polyoxometalate (POM) clusters have been synthesized and employed as electrode materials in lithium ion batteries. The Anderson cluster [MnMo6 O24 ](9-) is functionalized with Tris (NH2 C(CH2 OH)3 ) moieties, giving the new organic-inorganic hybrid [N(nC4 H9 )4 ]3 [MnMo6 O18 {(OCH2 )3 CNH2 }2 ]. The compound is then covalently attached to carboxylic acid-functionalized SWNTs by amide bond formation and the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 48 publications
(40 reference statements)
2
55
0
Order By: Relevance
“…In this temperature range, the GO‐IL and GO‐IL‐P 2 Mo 18 nanocomposite show weight losses of 36.86 and 21.45 wt %, respectively, which is associated with the thermal degradation of organic groups such as −COOH, −OH, and so on. Assuming that the weight losses of the organic groups are the same in the GO‐IL and GO‐IL‐P 2 Mo 18 , the content of P 2 Mo 18 in the GO‐IL‐P 2 Mo 18 nanocomposite can be estimated to be approximately 46.72 wt % …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this temperature range, the GO‐IL and GO‐IL‐P 2 Mo 18 nanocomposite show weight losses of 36.86 and 21.45 wt %, respectively, which is associated with the thermal degradation of organic groups such as −COOH, −OH, and so on. Assuming that the weight losses of the organic groups are the same in the GO‐IL and GO‐IL‐P 2 Mo 18 , the content of P 2 Mo 18 in the GO‐IL‐P 2 Mo 18 nanocomposite can be estimated to be approximately 46.72 wt % …”
Section: Resultsmentioning
confidence: 99%
“…Our group first studied a nanocomposite of pyrene‐modified POMs and SWNTs, and its application as an LIB anode material showed improved charge‐transfer efficiency . Later, we reported the preparation of Anderson covalently functionalized SWNTs, and electrochemical analyses indicated that the resultant nanocomposite had a high discharge capacity of up to 932 mAh g −1 at a current density of 0.5 mA cm −2 with excellent stability . Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…[31] POM-organo-functionalization critically relies on stable cluster architectures that can be deployed in chemicallyd emanding reaction environments. [36] Here, we show how the covalenta ttachment of 2,2'-bipyridine to Anderson anionsa nd subsequent coordination of iridium complexes gives accesst op hotosensitizer-HER-catalyst dyadsc apableo fs ustained visible-light-drivenh ydrogen evolution. [36] Here, we show how the covalenta ttachment of 2,2'-bipyridine to Anderson anionsa nd subsequent coordination of iridium complexes gives accesst op hotosensitizer-HER-catalyst dyadsc apableo fs ustained visible-light-drivenh ydrogen evolution.…”
mentioning
confidence: 86%
“…The activated proton allowed grafting of tris-NH 2 , tris-CH 3 and tris-CH 2 CH 3 ligands that cap a tetrahedral cavity instead of the heteroatom by covalently binding to two μ 3 -O atoms and one μ 2 -O atom on the planar Anderson-Evans surface giving the single-sided χ-isomer [190]. The formed product allows in theory further post-functionalization (Figure 7, C3) as observed with δ-isomers (section 5.2).…”
Section: Synthesis Of Single and Double-sided χ-Isomersmentioning
confidence: 99%
“…The following paragraphs looks into some interesting hybrid tris-functionalized compounds in terms of structure and crystal packing with a special emphasis on the Mn III Mo 6 system. -CH2OH (S, χ-isomer) nr [190] Mn III Mo6…”
Section: An Overview Of Tris-functionalized Hybrid Structuresmentioning
confidence: 99%